Public Service Leadership Organization: Work Motivation and Work Productivity in Library Organization Within Organizational Behavior Perspectives - Bakhtiyar, Bakhtiyar (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2019)
The aim of the study is to find: (1) The importance of library organization leadership. (2) The importance of the subordinates motivation in the library environment. (3) Leader role in increasing work productivity at the library. The research object is focused on discussion of leadership content, work motivation and librarians work productivity. The scope of the study is based on the embodiment of leadership management and leader active role provides a variety of motivations, in order to achieve optimal work productivity. This study using historical approach, primary information sources as primary data and research methods using library research. The analysis using qualitative descriptive research, content analysis and observation as complement data to support theoretical construction. The results are; (1) The significance of library organization leaders are: (a) Leaders give meaning to the realization of organizational behaviours that has realistic and relevant goals to be achieved. (b) The leader binds, controls the subordinates and provides work motivation. (c) Leaders must have and use their abilities to realize the achievement of library organization goals effectively and efficiently. (d) Leaders always introspect and improve themselves, in order to become role models. (2) Work motivation is a combination of desire and energy, which is the biggest factor in realizing and overtaking the goals of library organizations. (3) The role of leaders in increasing work productivity within the organization is a top priority.